2017
DOI: 10.3892/br.2017.949
|View full text |Cite
|
Sign up to set email alerts
|

The combination of CRP isoforms with oxLDL decreases TNF-α and IL-6 release by U937-derived macrophages

Abstract: Abstract. C-reactive protein (CRP) and oxidized low density lipoprotein (oxLDL) serve major roles at both early and advanced stages of atherosclerosis. CRP exists in two isoforms, monomeric (m) and pentameric (p), that bring about pro-or anti-inflammatory effects in macrophages. In addition, CRP may form a complex with oxidized low-density lipoprotein (oxLDL) via phosphatidylcholine, thus decreasing its pro-inflammatory effects within macrophages. The aim of the present study was to investigate the single and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
2
11
0
1
Order By: Relevance
“…Such effects might be mediated by the downregulation of cytokines known to induce IFN-γ production, including IL-12 and IL-18 (27,28). This was further supported by the increased levels of IL-4, which has been previously demonstrated to suppress IL-12/IL-18 secretion (25,26), under most single and combined treatments, the least effect being observed following treatment with oxLDL.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Such effects might be mediated by the downregulation of cytokines known to induce IFN-γ production, including IL-12 and IL-18 (27,28). This was further supported by the increased levels of IL-4, which has been previously demonstrated to suppress IL-12/IL-18 secretion (25,26), under most single and combined treatments, the least effect being observed following treatment with oxLDL.…”
Section: Discussionmentioning
confidence: 64%
“…SA1x and SA2x served as single and double concentration controls for sodium azide present in mCRP and mCRP/pCRP, respectively. The adopted concentrations were chosen based on previous literature (26).…”
Section: Differentiation Of U937 Cells Into Macrophages Human Monocymentioning
confidence: 99%
“…The induction of inflammation in U937-derived macrophages in vitro is a reliable indication of the activity of mCRP, and increases in IL-6 and TNF-α are attributed to detrimental tissue-related complications ( 20 ). Here we showed that both acetylcholine and nicotine were able to attenuate, significantly, both TNF-α and IL-6 activity, whilst neither tacrine nor the targeting antibodies were effective.…”
Section: Discussionmentioning
confidence: 99%
“…When CRP levels become elevated in atheroma, this leads to the induction of IL-6 by macrophages indicating that CRP may have a direct effect on IL-6 release ( 99 ). Krayem et al ( 100 ) found that a combination of mCRP, nCRP, and oxLDL decreases IL-6 production in a model of atherosclerosis. This triple combination suggests that nCRP might downregulate the IL-6 release by macrophages that have been stimulated by both mCRP and oxLDL.…”
Section: Crp Isoforms and Inflammatory Cytokinesmentioning
confidence: 99%
“…However, there is some contradictory evidence showing a potential inhibitory effect of CRP on TNF-α production, suggesting that there could be a negative feedback mechanism whereby elevated levels of CRP inhibit further stimulation of CRP by reducing the TNF-α production ( 114 ). A combination of mCRP, nCRP, and oxLDL also causes a decrease in both TNF-α and IL-6 production in a macrophage model of atherosclerosis ( 100 ). This triple combination suggests that nCRP might downregulate TNF-α and IL-6 production by macrophages stimulated by both mCRP and oxLDL.…”
Section: Crp Isoforms and Inflammatory Cytokinesmentioning
confidence: 99%